Estudo dos conhecimentos evidenciados por alunos dos cursos de licenciatura em Matemática e Física participantes do PIBID-PUC/SP - Correia, Gerson dos Santos (2012)
This research is embedded in the context of initial teacher education, being a product of the project approved Observatory Education Program Capes. Intended to investigate the knowledge evidenced by students of the degree in Mathematics and Physics project participants approved the PUC / SP Institutional Scholarship Program Initiation to Teaching - PIBID Capes. Studies were undertaken from the perspective of CNE / CP 09/2001 and the National Curriculum Guidelines for Teacher Training Basic Education in academic level, Bed (Bachelor of Education) courses, full graduation, in order to understand the perspectives of public policies on teacher training and the knowledge which the future teacher must have for teaching. Not only presents this paper the PIBID program, which aims to stimulate the initiation and participation of students from Bed courses into teaching in elementary public schools, but also the approved project by PUC / SP. The Mizukami s studies were used as theoretical basis on the teachers training with a view at the training process for teaching, which emerge and constitute the exercising of teaching practice, and the notions about the kinds of knowledge and discussion of the knowledge basis for teaching Shulman. Data collection was performed using the partial report of the intervention phase of the Subproject PIBID-PUC/SP of Bachelor Mathematics Science courses and from the meeting of scholarship scholars participating in the project. Data analysis consisted of an episode of intervention and assessment to identify evidenced knowledge by scholarship scholars in an elementary public school. The results show evidences to the knowledge basis for teaching Shulman in intervention activities developed by scholarship scholars, such as content knowledge, which is the domain of the subject developed, general pedagogical knowledge, which includes knowledge of theories and principles related to the processes of teaching and learning, and pedagogical content knowledge, which happens by combining the content domain with the pedagogical activity intervention